From villainous vixen to feminist icon: a critical analysis of Lilith in Shadowhunters (2016–2019) and The Chilling Adventures of Sabrina (2018–) - Lauwrens, Jennifer (University of Pretoria, 2021)
Dissertation (MA)--University of Pretoria, 2020.